Injunksi Mareva: Rahmat Atau Mudharat – Raja Letchumi Ramarajoo Lwn. The Hong Kong & Shanghai Banking Corporation - Abdul Rashid, Talat Mahmood bin (Journal of Malaysian and Comparative Law, 2019)
Mareva Injunction.